Prospective associations between parental feeding practices used in toddlerhood and preschool children's appetite vary according to appetite avidity in toddlerhood. (1st June 2023) - Kininmonth, Alice R.; Herle, Moritz; Haycraft, Emma; Farrow, Claire; Croker, Helen; Pickard, Abigail; Edwards, Katie; Blissett, Jacqueline; Llewellyn, Clare
Abstract: Parental feeding practices are a key modifiable component of children's food environments. Evidence suggests that certain feeding practices may differentially influence children's eating behaviour or weight, depending on the child's temperament (e.g. emotionality). Building on this work, we tested the hypothesis that feeding practices during toddlerhood influence children's developing eating behaviours differently, depending on their appetite avidity (which is characterised by a larger appetite and greater interest in food). Data were from Gemini, a population-based cohort of British twin children born in 2007. Parental feeding practices were assessed at 15/16-months, and child appetite at 15/16-months and 5-years, using validated psychometric measures (n = 1858 children). Complex samples general linear models examined prospective associations between PFPs at 15/16-months and child appetitive traits at 5-years, adjusting for clustering of twins within families and for the corresponding child appetitive trait at 15/16-months, difference in age between timepoints, child sex, gestational age, and socioeconomic status. Moderation analyses revealed that pressuring a child to eat led to greater increases in emotional overeating from 15/16-months to 5-years, only for children with high (1 SD above the mean: B = 0.13; SE± = 0.03, p < 0.001) or moderate emotional overeating (mean: B = 0.07 ± 0.03, p < 0.001) in toddlerhood. Greater covert restriction predicted greater reductions in emotional overeating and food responsiveness from 15/16-months to 5-years, only for children with high emotional overeating (1 SD above the mean: B = −0.06 ± 0.03, p = 0.03) and low food responsiveness (1 SD below the mean: B = −0.06 ± 0.03, p = 0.04) in toddlerhood. These findings are consistent with the hypothesis that children with a more avid appetite in toddlerhood are differentially affected by parental feeding practices; caregivers of toddlers may therefore benefit from feeding advice that is tailored to their child's unique appetite.